PENGALIAN, KENEGARIAN KOTO RAJO, KECAMATAN KUANTAN HILIR, KABUPATEN KUANTAN SINGINGI - Evizariza, Evizariza; Hermansyah, Hermansyah; Juswandi, Juswandi (JURNAL PUSTAKA BUDAYA, 2017)
AbstractThis study aims to examine the religious valuesÂ Â  and economic valuesÂ Â  of the people on the game Skate âin the village of Multiplication, Kenegarian Kotorajo,.Kuantan Hilir Subdistrict, District Singingi. This study used a descriptive method, a method that is used describe skating in the village folk games Multiplication, Kenegerian Koto tengah Seberang Hilir District of Kuantan, Kuantan District Singingi. Correctly, so that the valuesÂ Â  contained in the folk games of skating it can be seen clearly. There are several data collection techniques that I use to understand a descriptive study with interview techniques, observation. The results of this study are yamg religious valuesÂ Â  contained in each game is started skating people skating games basmalah always reading and praying, besides instilling honesty, and mutual work sama. Nilai-economic valuesÂ Â  contained in the folk games of skating, in the execution of the game can boost the economy of society with digalakkannya social economy. Keywords: religious valuesÂ Â  and economic valuesAbstrakPenelitian ini bertujuan untuk meneliti nilai nilai Agama dan nilai ekonomi pada permainan rakyat Seluncurâ di Desa Pengalian, Kenegarian Kotorajo. Kecamatan Kuantan Hilir, Kabupaten Singingi. Penelitian ini menggunakan metodeÂ  deskriptif, yaitu metode yang digunakan menggambarkan permainan rakyat seluncur di Desa Pengalian, Kenegerian Koto Tengah Kecamatan Kuantan Hilir Seberang, Kabupaten Kuantan Singingi. Secara benar, sehingga nilai-nilai yang terkandung dalam dalam permainan rakyat seluncur itu dapat diketahui dengan jelas. Ada beberapa teknik pengumpulan data yang penulis pakai untuk memahami sebuah penelitian yang bersifat deskriptif dengan teknik wawancara, observasi. Hasil Penelitian ini adalah nilai-nilai agama yang terdapat pada permainan rakyatÂ  seluncur adalah setiap mengawali permainan seluncur selalu membaca basmalah dan berdoa,Â  selain itu menanamkan sikap jujur, dan saling bekerja sama. Nilai-nilai ekonomi yang terdapat pada permainan rakyat seluncur, dalam pelaksanaan permainan tersebut dapat meningkatkan perekonomian masyarakat dengan digalakkannya ekonomi kerakyatan.Kata kunci: Nilai agama dan Nilai-nilai ekonomi